Assessing the clinical value of the Kruger strict morphology criteria over the World Health Organization fourth edition criteria - Gal Wald, B.A; Nahid Punjani, M.D., M.P.H; Russell Hayden, M.D; Miriam Feliciano, B.Sc; Vanessa Dudley, M.S.H.S; Marc Goldstein, M.D., D.Sc (Elsevier, 2021)
Objective: To assess if the newer Kruger strict morphology (WHO5; normal ≥4%) adds any clinical value beyond the criteria of the World Health Organization fourth edition (WHO4; normal ≥14%). Design: Retrospective study. Setting: Tertiary hospital. Patient(s): Men without known azoospermia who had semen analysis (SA) collected over a 10-year period of time. Intervention(s): Morphology classification under Kruger WHO5 strict criteria and WHO4 criteria. Main Outcome Measure(s): Correlation between the WHO5 and WHO4 morphological classifications. Result(s): A total of 4,510 SAs were identified during the study period. Of these, both Kruger WHO5 and WHO4 morphologies were included in 932 SAs (20.7%) from a total of 691 men. The median age of the men was 37 years (interquartile range, 32.0-43.8 years). The mean (±SD) semen volume, sperm concentration, and motility were 2.6 ± 1.4 mL, 50.0 ± 35.6 × 106/mL, and 53.1% ± 18.6%, respectively. The correlation between the WHO4 and WHO5 morphology assessments was high (Spearman correlation coefficient = 0.94). Only 545 (58.5%) of 932 SAs had abnormal Kruger WHO5 morphology, of which 543 (99.6%) of 545 also had abnormal morphology by the WHO4 criteria. Conclusion(s): The Kruger WHO5 and WHO4 morphologic criteria correlate closely. Only two men (0.4%) with an abnormal Kruger morphology had normal WHO4 morphology. Given the limited predictive value of sperm morphology, the additional cost and effort of Kruger criteria may not be warranted in lieu of, or in addition to, the WHO4 classification.